Book review: Soldier’s Paradise, Militarism in Africa after Empire - Szakali, Miklós (Journal of Central and Eastern European African Studies, 2025)
The book provides a comprehensive approach to the circumstances that led to the emergence of Nigerian militarism and successive military dictatorships, with an outlook on other former British colonies. It introduces the most important Nigerian military leaders and provides insight into their aspirations, ways of thinking and their real results. In this way we can have a better insight why militarism and discipline became an ideology and rose to the level of political objectives. The author also presents the attempts and pitfalls of creating and operating the legal system of militarism. Militarism regarded law as the second pillar of the system, with which it could govern the country and exercise military power in a decisive and internationally acceptable manner. However, it was not a very simple and smooth cooperation at all, many difficulties (power struggle, colonial legacy, etc.) influenced the outcome of development. Considering all this, we cannot be surprised at the rather limited progress that has been made. The book reinforces the approach that all circumstances must be carefully examined before criticizing or judging a former colonial country from a European, Western perspective. I especially recommend Soldier’s Paradise to anyone who wants to explore Nigeria’s post-colonial history based on authentic documents. I believe that through the author’s findings, we can better understand the current situation of African countries. <pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Translation" data-ved="2ahUKEwjU1ern-fKKAxU4UVUIHd4PB9wQ3ewLegQIChAU" aria-label="Translated text: I believe that through the author’s findings, we can better understand the current situation of African countries."> <pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Translation" data-ved="2ahUKEwjU1ern-fKKAxU4UVUIHd4PB9wQ3ewLegQIChAU" aria-label="Translated text: The book reinforces the approach that all circumstances must be carefully examined before criticizing or judging a former colonial country from a European, Western perspective.">